X-ray photoelectron spectroscopic investigations of Cu2O nanoparticles - Nikesh, V. V.; Mandale, A. B.; Patil, K. R.; Mahamuni, Shailaja (Materials Research Bulletin, 2005)
Cuprous oxide nanoparticles of five different sizes were obtained by electrochemical as well as chemical routes. Various capping agents were used to passivate the nanoparticles. X-ray diffraction studies show formation of single phased, cubic Cu2O nanoparticles. X-ray photoelectron spectroscopic studies indicate formation of CuO phase on the surface of Cu2O nanoparticles for uncapped as well as for those, capped by tetraoctylammonium bromide. On the other hand polyacrylamide and polyvinyl pyrrolidone capped samples did not show presence of CuO. X-ray photoelectron spectroscopy also indicates formation of a Cu2+ complex with the capping material on the surface of Cu2O nanoparticles. The results were discussed in terms of capability of passivation of various additives. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Nanostructures; Oxides; photoelectron spectroscopy; Surfaces

One pot synthesis, growth mechanism and optical properties of Zn1-xCdxSe graded core/shell and alloy nanocrystals - Sonawane, Kiran G.; Patil, K. R.; Mahamuni, Shailaja (Journal of Luminescence, 2013)
Comparatively higher photoluminescence yield along with robustness of core/shell semiconductor nanocrystals make them attractive candidates for studying intricate quantum size effects. Here, we report, one pot synthesis of Zn1-xCdxSe graded core/shell structures by exploiting change in the reactivity of precursors. Optical and structural measurements indicate formation of graded structure. Growth mechanism probed by inductively coupled plasma atomic emission spectroscopy shows formation of graded core/shell structure, with CdSe rich core and ZnSe rich shell. Annealing these nanocrystals, in chemical bath, leads to diffusion of Cd from core to shell region. Formation of Zn1-xCdxSe alloy is also observed in X-ray photoelectron spectroscopic measurements, confirming the diffusion of Cd from core to shell region. Substantially high photoluminescence quantum efficiency of 60% with narrow line width of about 27 nm, was observed and is attributable to the reduced strain due to graded core/shell structure. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Graded core/shell; II-VI Semiconductor; Luminescence; Optical properties; Semiconductor alloy